2021
DOI: 10.1128/mra.00024-21
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Aureimonas sp. Strain OT7, Isolated from Human Skin

Abstract: Aureimonas sp. strain OT7 was isolated from human skin. This strain can grow on Triton X-100. Here, we present the complete whole-genome sequence of this species, which has one chromosome of 4,181,223 bp (G+C content, 65.05%). Analysis of the Aureimonas sp. strain OT7 genome sequence indicated potential for autotrophic growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…OT7, supported by high bootstrap values (Figure S1). Strain OT7, isolated from human skin, and strain ON-56566, isolated from patient blood culture, were reported to belong to the same species clade that is separated from the A. altamirensis type strain [41]. Consistent with the 16S rRNA data, a phylogenomic analysis indicated that A. frigidaquae and "A. fodinaquatilis" were the species most closely related to A. altamirensis.…”
Section: Phylogenetic Analysismentioning
confidence: 73%
See 2 more Smart Citations
“…OT7, supported by high bootstrap values (Figure S1). Strain OT7, isolated from human skin, and strain ON-56566, isolated from patient blood culture, were reported to belong to the same species clade that is separated from the A. altamirensis type strain [41]. Consistent with the 16S rRNA data, a phylogenomic analysis indicated that A. frigidaquae and "A. fodinaquatilis" were the species most closely related to A. altamirensis.…”
Section: Phylogenetic Analysismentioning
confidence: 73%
“…The four strains of environmental origin formed a shared cluster that was distinct from the isolates detected in clinical samples [31,32,37,38,41]. Within the genus, A. frigidaquae and "A. fodinaquatilis" were found to be the closest related species.…”
Section: Phylogenetic Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…Ethical approval for subject sampling was granted by the institutional review board of Changwon National University. Sanger sequencing of the 16S rRNA gene amplicon with primers 27F (5′- AGAGTTTGATCCTGGCTCAG -3′) and 1492R (5′- GGTTACCTTGTTACGACTT -3′) ( 3 ) yielded unidentifiable overlapping peaks with partially recognizable nucleotide sequences at the 5′ and 3′ ends. The amplification conditions were the same as those described previously ( 4 ).…”
Section: Announcementmentioning
confidence: 99%
“…Ethical approval for subject sampling was granted by the institutional review board of Changwon National University. Sanger sequencing of the 16S rRNA gene ( 4 ) using the V1 to V9 region (i.e., with primers 27F and 1492R) enabled the identification of TT17 as belonging to the genus Brevundimonas .…”
Section: Announcementmentioning
confidence: 99%